HAK ATAS PENDIDIKAN DAN HAK BUDAYA MASYARAKAT ADAT (TINJAUAN HAK MASYARAKAT ADAT DI JEPANG DAN INDONESIA): INDIGENOUS PEOPLE RIGHTS IN CULTURE & EDUCATION (A REVIEW OF RIGHTS FOR INDIGENOUS PEOPLE IN JAPAN AND INDONESIA) - Notoprayitno, Maya Indrasti; Permanasari, Arlina; Nrangwesti, Ayu; Zuhra, Amalia; Fitriliani, Yulia (Fakultas Hukum Universitas Trisakti, 2024)
Access of Indigenous children to education remains a problem when there is discrimination in learning, treatment, and the use of the language and culture in schools. This impacts on the achievement of education for all. Discriminatory fulfilment of the right to education for Indigenous children is not only experienced by developing countries, but in fact indigenous children in developed countries experienced the same thing. The Ainu tribe children in Japan still experiences discrimination in the world of education, but in contrast to the Anak Dalam tribe in Indonesia, the Indonesian Government has sought to obtain their rights. The role of the government in fulfilling the right to education is very important as the entity responsible for upholding human rights. The government's role in inclusive education raises the issue of the rights of indigenous children in the fields of culture and education to a more real significant and realistic.